Implementation of Islamic Religious Education in Character Formation at the Salafiyah Ula Nashrus Sunnah Madrasah in Madiun City - Fitrian Nurazizah; Maulid Roikhan Mustafit; Azzah Ayu Azzahroh; Fretina Ananta Nurya Putri; Aci Ardian (CV. Bimbingan Belajar Assyfa, 2024)
This study aims to examine the role of Islamic Religious Education (PAI) in shaping the religious character of students at Madrasah Salafiyah Ula Nashrus Sunnah, Madiun City. The research is motivated by concerns about the decline in students’ moral and spiritual values due to the influence of globalization, social media, and the weakening role of the family as the primary educator. This condition highlights the importance of Islamic Religious Education in developing students’ religious character from an early age. The study employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The findings reveal that PAI plays a significant role in instilling religious character through the integration of Islamic values into the curriculum, teachers’ exemplary behavior, daily worship practices, and social activities such as charity (infak) and cooperation among students. The Islamic character values developed include silat ar-rahmi, ukhuwah, al-‘adalah, husnudzan, tawadhu, amanah, iffah, and al-munfiqun. These values shape students’ religious attitudes as reflected in their morality, discipline, and sense of responsibility, both within and outside the school environment. However, this process faces challenges such as diverse family backgrounds and the negative influence of digital environments. The study concludes that the success of religious character formation through PAI largely depends on the synergy between teachers, families, and the social environment, as well as the implementation of contextual learning strategies that touch upon students’ spiritual aspects.